Christian Mission, Spiritual Leadership and Personality Development of the Digital Generation - Joni Manumpak Parulian Gultom; Vicky Baldwin Goldsmith Dotulong Paat; Otieli Harefa (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2022)
Spiritual leadership has experienced a significant correction of service responsibilities for God's church. Several reasons are advances in information technology, social media, and financial problems. On the other hand, the digital generation is the majority of the congregation. The facts show that 6 out of 10 people (59%) leave the Christian faith in the first decade of adulthood, and the number 44% - 52% do not go to church. The personality of the digital generation tends to be eroded, while the church leadership seems to have lost the enthusiasm to reach them. The question is how to build the resilience of spiritual leaders in the digital age? What kind of implications and approaches in developing the personality of the Digital Generation can take? The purpose is to describe the steps to build spiritual leadership resilience and explain the implications and mission approaches of digital generation personality development. Research is a qualitative descriptive method. The results are building Spiritual Leadership Resilience by upgrading oneself in contemporary leadership, building friendships, synergizing with other spiritual practitioners, and building worship praise as a medium for spiritual experience. The implications for the digital generation are: Developing the three vocations of the church, building intergenerational relationships and leadership spirit, generating gifts and role effectiveness, and emphasizing the meaning and fulfillment of future leadership functions.